Structural Control of Charge Storage Capacity to Achieve 100% Doping in Vapor Phase-Polymerized PEDOT/Tosylate - Rehmen, Junaiz (ACS Omega, 2019)
[Image: see text] Vapor phase polymerization (VPP) is used to fabricate a series of tosylate-doped poly(3,4-ethylenedioxythiophene) (PEDOT) electrodes on carbon paper. The series of VPP PEDOT/tosylate coatings has varying levels of crystallinity and electrical conductivity because of the use (or not) of nonionic triblock copolymers in the oxidant solution during synthesis. As a result, the impact of the structure on charge storage capacity is investigated using tetra-n-butylammonium hexafluorophosphate (0.1 M in acetonitrile). The ability to insert anions, and hence store charge, of the VPP PEDOT/tosylate is inversely related to its electrical conductivity. In the case of no nonionic triblock copolymer employed, the VPP PEDOT/tosylate achieves electrochemical doping levels of 1.0 charge per monomer or greater (≥100% doping level). Such high doping levels are demonstrated to be plausible by molecular dynamics simulations and density functional theory calculations. Experiments show that this high doping level is attainable when the PEDOT structure is weakly crystalline with (relatively) large crystallite domains.